Hubungan Pengetahuan, Sikap, dan Akses Media Sosial dengan Perilaku Seksual Remaja Perempuan - Viviencia M. A. Masae; Imelda F. E. Manurung; Deviarbi Sakke Tira (Media Kesehatan Masyarakat, 2019)
Teen sexual behavior is any behavior that is driven by sexual desire either committed themselves, with the opposite sex or same-sex marriage in the absence of religion law. Regional Public Hospital of Kalabahi’s data found that in 2017, 10 teenagers had sexual before marriage. Factors that encourage teens women committing deviant sexual behavior due to the lack of knowledge about sexual behavior, positive attitude toward sexual behavior as well as access to social media on adolescent sexual behavior. The purpose of this research was to analyze the relationship of knowledge, attitudes and social media access with the sexual behavior of adolescent women in SMA Negeri 1 Kalabahi 2017. Type of this research was an analytical survey using cross-sectional technique. The population in this research consisted of 218 woman student in SMA Negeri 1 Kalabahi. The sample in this study was 140 students selected by using simple random sampling. The results of the analysis suggested that knowledge (p-value = 0.000), attitude (p-value = 0.000), and access to social media (p-value = 0.000) were associated with sexual behavior in adolescent women in SMA Negeri 1 Kalabahi 2017. Education to increase knowledge among female teens about teen sexual behavior as well as establishing related rules for social media access in school are necessary.